Experimental and numerical studies on the optimal design of tuned mass dampers for vibration control of high-rise structures. (15th May 2020) - Liu, Yanhui; Wang, Kan; Mercan, Oya; Chen, Huating; Tan, Ping
Highlights: An optimal design method for the TMD design is presented in frequency domain based on genetic algorithm. The proposed method performs well in reducing the structural vibrations under wind and earthquake excitations while limiting the TMD stroke. The proposed method improves the reliability of the TMD and reduces the probability of failure. A permanent-magnet eddy current TMD was designed with the optimization method, built and tested. The shake table tests confirmed the ability of the proposed optimization method. Abstract: The use of Tuned Mass Damper (TMD) is effective in reducing the vibration response of the high-rise structures and in improving the structural comfort and safety under wind and earthquake excitation. However, it is occasionally difficult to use TMD for a given vibration control project when the available structural space cannot meet the requirements for the stroke of the designed TMD. If the TMD could be designed with a reduced stroke requirement, not only it will make the resign design a feasible vibration control option but also a cost-effective one. This paper presents an optimal design method for the TMD design, where in frequency domain and using genetic algorithm under random excitation the control effect of TMD is treated as the optimization objective and the stroke of TMD is chosen as the constraint condition. A 168-meter high tower with TMD was used as an engineering example for a numerical study, where the optimization method was used to obtain the TMD design parameters. Additionally, a TMD with an eddy current damper was designed according to optimal design method and was introduced to a 7-story scaled down structural model. Shaking table tests were performed to evaluate the performance of the designed TMD using the optimization design method, and compared against the one designed by Den Hartog's formula. The numerical simulations show that the TMD designed with the proposed method to achieve a limited TMD stroke has a similar control effectiveness in comparison to the Den Hartog's solution. While achieving a good control performance, the proposed design method also effectively limits the TMD stroke where the peak TMD displacement of the proposed design method is 0.78 m, much smaller than that obtained by Den Hartog's formula, 0.95 m. Similar results are observed in the experimental study. Therefore, the proposed optimal design method can improve the reliability of the TMD and it reduces the probability of failure.